Preterm infant retinal OCT markers of perinatal health and retinopathy of prematurity - Mangalesh, Shwetha; Toth, Cynthia A. (Frontiers in Pediatrics, 2023)
The increasing survival of preterm infants has led to the importance of improving long-term outcomes associated with preterm birth. Antenatal and perinatal insults not only impact mortality, but also long-term disability. While in the intensive care nursery, preterm infants are also exposed to various stressors that lead to long-term cognitive deficits. It is therefore critical to identify early, low-stress, non-invasive biomarkers for preterm infant health. Optical coherence tomography (OCT) is a powerful imaging modality that has recently been adapted to the infant population and provides noninvasive, high-resolution, cross-sectional imaging of the infant eye at the bedside with low stress relative to conventional examination. In this review we delve into discussing the associations between preterm systemic health factors and OCT-based retinal findings and their potential contribution to the development of non-invasive biomarkers for infant health and for retinopathy of prematurity (ROP).